Alleviative Effect of Alpha-Lipoic Acid on Cognitive Impairment in High-Fat Diet and Streptozotocin-Induced Type 2 Diabetic Rats - Ko, Chih-Yuan; Xu, Jian-Hua; Lo, Yangming Martin; Tu, Rong-Syuan; Wu, James Swi-Bea; Huang, Wen-Chung; Shen, Szu-Chuan (Frontiers in Aging Neuroscience, 2021)
Background: The intricate relationship between type 2 diabetes mellitus (T2DM) and Alzheimer’s disease (AD) suggests that insulin is involved in modulating AD-related proteins. Alpha-lipoic acid (ALA) can improve insulin resistance (IR) in diabetic rats. However, the role of ALA in alleviating the cognitive decline of T2DM is not yet clear. This study examined the ameliorative effect of ALA on cognitive impairment, cerebral IR, and synaptic plasticity abnormalities in high-fat diet (HFD) plus streptozotocin (STZ) induced diabetic rats. Methods: The HFD/STZ-induced T2DM male Wistar rats were orally administered with ALA (50, 100, or 200 mg/kg BW) once a day for 13 weeks. Abilities of cognition were measured with a passive avoidance test and Morris water maze. Specimens of blood and brain were collected for biochemical analysis after the rats were sacrificed. Western blotting was used to determine protein expressions in the hippocampus and cortex in the insulin signaling pathways, long-term potentiation, and synaptic plasticity-related protein expressions. Results: ALA improved hyperinsulinemia and the higher levels of free fatty acids of the T2DM rats. Behavioral experiments showed that the administration of ALA improved cognitive impairment in HFD/STZ-induced T2DM rats. ALA ameliorated insulin-related pathway proteins (phosphoinositide 3-kinase, phospho-protein kinase B (pAkt)/Akt, and insulin-degrading enzyme) and the long-term potentiation pathway, as well as synaptic plasticity proteins (calmodulin-dependent protein kinase II, cyclic AMP response element-binding protein, and postsynaptic density protein-95) of the cerebral cortex or hippocampus in HFD/STZ-induced T2DM rats. Conclusion: Our findings suggested that ALA may ameliorate cognition impairment via alleviating cerebral IR improvement and cerebral synaptic plasticity in diabetic rats.